Cardiac manifestations of dengue fever in pediatrics age group - Menwal, Upasana; Rawat, Anil; Rawat, Anurag; Chandar, Vipan (Indian Journal of Child Health, 2020)
Background: Dengue infection is a serious public health concern in tropical and subtropical regions of the world. Cardiac involvement is a known but rare complication of dengue. Electrocardiogram (ECG) and 2D echocardiogram (ECHO) are preferred non invasive instant diagnostic tool to evaluate the status of heart in dengue infection. Objectives: The present study was carried out to confirm the cardiac manifestation in dengue fever, along with its correlation with the severity of the disease. Materials and Methods: A total of 60 subjects were included over a period of 1-year time from inpatient and outpatient departments presenting with clinical features suggestive of dengue and further confirmed by positive serology test of IgM and/or NS1 antigen by rapid and/or by ELISA method. Cardiac manifestations were analyzed with the help of ECG and 2D ECHO in all serologically confirmed cases. Results: 16 out of 60 cases had cardiac findings in the form of tachycardia, bradycardia, and myocarditis. ECG showed some nonspecific findings like sinus tachycardia followed by sinus bradycardia. Myocarditis diagnosed by ECHO as ejection fractions